Peran Guru Dalam Tumbuh Kembang Anak Tunanetra Majemuk di Yayasan Pendidikan Dwituna Rawinala Jakarta Timur - Margareth Kartini Brades (Peneliti.net, 2023)
This study aims to identify the teacher's role in assisting multiple visual impairment children in their process of growth and development along with uncovering the methods used by teachers at Dwituna Rawinala Education Foundation. This research is dissected by using Robert Linton's role theory and Paulo Freire's theory of humanistic approach in education. Dwituna Rawinala Education Foundation was founded in 1973 by several activists from the Javanese Christian Church Jakarta with the aim of providing proper education for children who have two or more disabilities especially disability in their sense of sight Multiple Disabilities Visually Impairment (MDVI). The teacher applies different teaching methods to each of their multiple visually impairment students and teaches basic humanistic activities. With the aim of supporting the growth and development of multiple visually impairment children in order for them to become independent individuals and able to live alongside others in a social environment.